Предмет: Алгебра, автор: lanasen99

а) 7√3-√48+√27=

б) √2(√8+4√2)=

в) (√3+5)^2=

г) (√5+√3)(√5-√3)=

Ответы

Автор ответа: hote
0

displaystyle 7sqrt{3}-sqrt{48}+sqrt{27}=7sqrt{3}-sqrt{16*3}+sqrt{9*3}=\\=7sqrt{3}-4sqrt{3}+3sqrt{3}=6sqrt{3}

displaystyle sqrt{2}(sqrt{8}+4sqrt{2})=sqrt{2}(2sqrt{2}+4sqrt{2})=sqrt{2}*(6sqrt{2})=6*sqrt{2}*sqrt{2}=12

displaystyle (sqrt{3}+5)^2=sqrt{3}^2+2sqrt{3}*5+5^2=3+10sqrt{3}+25=28+10sqrt{3}

displaystyle (sqrt{5}+sqrt{3})(sqrt{5}-sqrt{3})=(sqrt{5})^2-(sqrt{3})^2=5-3=2

Похожие вопросы
Предмет: Қазақ тiлi, автор: Аноним